Adolescent tobacco coupon receipt, vulnerability characteristics and subsequent tobacco use: analysis of PATH Study, Waves 1 and 2. Issue Volume 27:Issue e1(2018) (22nd February 2018) - Rose, Shyanika W; Glasser, Allison M; Zhou, Yitong; Cruz, Tess Boley; Cohn, Amy M; Lienemann, Brianna A; Byron, M Justin; Huang, Li-Ling; Meissner, Helen I; Baezconde-Garbanati, Lourdes; Unger, Jennifer B
Abstract : Objectives: We examine adolescent receipt of tobacco coupons and subsequent tobacco use. Methods: Data were from the Population Assessment of Tobacco and Health (PATH) Study (2013–2015). We identified correlates of coupon receipt at Wave 1 (youth sample age 12–17 ; n = 13 651) including demographics, additional vulnerability factors that may place youth at risk of tobacco use and correlates of coupon receipt by channel. We examined associations of Wave 1 coupon receipt with Wave 2 tobacco use using weighted multivariable models. Results: Overall, 7.6% of US youth received tobacco coupons in the 6 months before Wave 1. Coupon recipients were more likely to be women, living outside urban areas, living with a tobacco user, current and former (vs never) tobacco users, having high internalising mental health symptoms and having a favourite tobacco advertisement. Coupons were received primarily through direct mail (56%), product packs (28%) and online (25%). Never tobacco users at Wave 1 who received coupons were more likely to be ever users at Wave 2 (adjusted OR (aOR)=1.42; 95% CI 1.06 to 1.91). Coupon recipients were more likely to use a new tobacco product between waves (aOR=1.67; 95% CI 1.18 to 2.36) and report past 30-day tobacco use at Wave 2 (aOR=1.81; 95% CI 1.31 to 2.49). Conclusions: One in 13 US youth (7.6%) received coupons. Vulnerable youth had the greatest odds of coupon receipt. Coupon recipients had greater odds of tobacco use among never users, trying a new tobacco product and current use. Coupon bans, limits on youth coupon exposure, stronger age verification, pack inserts or restricting coupon redemption may help reduce tobacco use among adolescents, particularly for those at greatest risk.